Ultrafast nonlinear optical response of Dirac fermions in graphene - Matthias Baudisch (Nature Portfolio, 2018)
Graphene possesses a nonlinear optical response arising from its electronic dispersion. Here, the authors measure the response of graphene to an ultrafast optical field and provide an explanation of the quantum dynamics of Dirac carriers mediating the material’s nonlinear response.